Assessing Students' Ability to Apply the Control of Variables Strategy When Engaged with Inquiry-Based Worksheets during the COVID Era - Eleni Petridou; Anastasios Molohidis; Euripides Hatzikraniotis (MDPI AG, 2022)
In this study, an inquiry-based sequence was designed, developed and implemented using facets of flipped classroom and aspects of inquiry learning using the ADDIE model. The sequence intends to promote the students' scientific literacy. The aim of this paper is to examine the effectiveness of specially designed inquiry-based online worksheets (e-WS) to actively engage students in the design of unconfounded experiments by applying the Control of Variables Strategy (CVS). Second-year senior high school (11th grade) students participated in an intervention in which facets of flipped classroom approach with asynchronous and synchronous distance learning sessions were adopted, during the COVID-19 lockdown. Results show that the flipped classroom approach with synchronous and asynchronous sessions was acceptable and adoptable by the students; the existence of probe questions in e-WS, combined with explicit reference to inquiry procedure enhanced students' awareness of scientific practice and on CVS, while at the end of the intervention, students were capable of applying the CVS in the design of unconfounded experiments.